Dimensions of CSR in Online Communication of Pharmaceutical Companies: A Comparative Study - Džupin Milan; Džupinová Zuzana (International Journal of Entrepreneurial Knowledge, 2019)
The article focuses on analysis of online communication of pharmaceutical companies in the field of CSR. It is based on the fact that there are specific segments in the economy, which are called sensitive sectors. Even though they are often perceived as irresponsible in their nature, there are effective communication tools, which can used to increase positive corporate image. The present study is a part of a larger research that we conducted in the segment of pharmaceutical industry. We used information about companies available on their websites as a research material. We reviewed their availability on websites, but we also reviewed the content on which companies usually focus in terms of social engagement. Our research was supposed to prove that there are considerable differences among companies in our sample. We analyzed (qualitative content analysis) collected data (basic corporate documents like mission, vision and corporate values) using statistical procedures. These documents are crucial to corporate strategies, and often deal with responsibility issues which are then transformed into business strategies, tactics and programs. According to the nature of the research the generalization of the information provided is relatively limited.